Mengintegrasikan Pemberdayaan Karyawan dan Strategi Pemasaran Digital untuk Meningkatkan Kepercayaan Pelanggan dan Keberlanjutan Bisnis di antara UMKM - Selamet, Selamet; Hartoyo, Hartoyo; Handayani, Juli Handayani (ICON Publisher, 2025)
This qualitative study explores how employee empowerment interacts with digital marketing strategies to enhance customer trust and business sustainability among micro, small, and medium enterprises (MSMEs). Using a phenomenological approach, in-depth interviews with MSME owners and employees reveal that empowerment fosters creativity, adaptability, and emotional engagement, which in turn strengthen digital brand communication and customer relationships. Empowered employees act as authentic brand representatives, translating organizational values into customer experiences through personalized digital interactions. The findings demonstrate that empowerment not only improves internal motivation but also serves as a catalyst for innovation and ethical marketing practices. Furthermore, the study highlights the strategic alignment between human resource management and marketing functions, showing that empowerment bridges the internal culture of collaboration with external customer trust. Theoretically, it extends empowerment discourse into the digital marketing domain, emphasizing human-centered innovation as a foundation for sustainable brand growth. Practically, it suggests that MSMEs integrate empowerment-based leadership and digital capability development to maintain authenticity and competitiveness in the digital economy.